The fauna of the family Bombycidae sensu lato (Insecta, Lepidoptera, Bombycoidea) from Mainland China, Taiwan and Hainan IslandsThe fauna of the family Bombycidae sensu lato (Insecta, Lepidoptera, Bombycoidea) from Mainland China, Taiwan and Hainan Islands - Wang, Xing; Wang, Min; Zolotuhin, Vadim V.; Hirowatari, Toshiya; Wu, Shipher; Huang, Guo-Hua (Zootaxa, 2015)
Seventy-seven species of family Bombycidae s. lat., belonging to 25 genera in three subfamilies, that have been recorded from China are listed and described, with illustrations of the adults, preimaginal stages (if available), and their genitalia. Keys to subfamilies and genera are provided. Two new genera and four new species are described, two subgenera are raised to generic status, seven new combinations are made, and one genus and six species are newly recorded from China. The new taxa are as follows: Rotunda Wang, X. & Zolotuhin, gen. nov., Comparmustilia Wang, X. & Zolotuhin, gen. nov., Triuncina daii Wang, X. & Zolotuhin, sp. nov., Triuncina xiongi Wang, X. & Zolotuhin, sp. nov., Gnathocinara boi Wang, X. & Zolotuhin, sp. nov. and Promustilia yajiangensis Wang, X. & Zolotuhin, sp. nov. The taxa newly recorded for China are: Sesquiluna Forbes, 1955; Trilocha friedeli Dierl, 1978; Bivincula kalikotei Dierl, 1978; Sesquiluna forbesi Zolotuhin & Witt, 2009; Mustilizans lepusa Zolotuhin, 2007; Smerkata brechlini (Zolotuhin, 2007) and Mustilia castanea Moore, 1879. The seven new combinations are: Rotunda rotundapex (Miyata & Kishida, 1990), comb. nov., Triuncina nitida (Chu & Wang, L.Y., 1993), comb. nov., Gunda sesostris (Vuillot, 1893), comb. nov., Smerkata fusca (Kishida, 1993), comb. nov., Comparmustilia sphingiformis (Moore, 1879), comb. nov., Comparmustilia semiravida (Yang, 1995), comb. nov., Comparmustilia gerontica (West, 1932), comb. nov.. The two subgenera raised to generic level are: Promustilia Zolotuhin, 2007, stat. nov. and Smerkata Zolotuhin, 2007, stat. nov.. The distributions of the species in China were determined and distributional maps provided. All type specimens of the new species described here are deposited in the College of Plant Protection, Hunan Agricultural University, China (HUNAU); Department of Entomology, South China Agricultural University, China (SCAU); Kyushu University Museum, Kyushu University, Japan (KUM), and Entomological Museum Thomas J. Witt, Munich, Germany (MWM).